EFFECT OF TWO FREEZING METHODS ON SPERM VIABILITY OF BOAR SEMEN - Carpio C., Mateo (2008)
The objective of this experiment was to evaluate the effect of two freezing methods on the spermatic viability of boar semen. Six collects (2 ejaculates per male) of three adult boars (Hampshire, Duroc and Landrace) were used. Immediately after the collection, volume, motility and spermatic concentration of each ejaculate were evaluated. Then, the semen was diluted with BTS solution (Beltsville Thawing Solution) and centrifuged at 1500 rpm for 10 min for plasma withdrawal. The pellet (spermatic portion) was diluted with freezing dilutor (A and B), cooled and equilibrated at 5 °C for two hours before freezing. The equilibrated semen was cryopreserved using two freezing methods: a) in pellets placing 0.25 ml aliquota of semen in holes prepared on the surface of a dry ice block for 20 min and then, pouring them in liquid nitrogen; and b) in straws of 0.5 ml exposing them at 7 cm over liquid nitrogen steam for 10 min (in a styrofoam box). The results showed no statistically differences amongst individual motility and live spermatozoa percentage in semen frozed in pellets (40.1 and 48.8%) as compared to straws (34.5 and 40.7%).